2023
DOI: 10.2147/jbm.s396026
|View full text |Cite
|
Sign up to set email alerts
|

Immune Thrombocytopenia Relapse in Patients Who Received mRNA COVID-19 Vaccines

Abstract: Background Immune thrombocytopenia (ITP) is a blood disorder in which antibodies coating platelets cause platelet destruction in the spleen with a resultant low platelet count and an increased tendency for bleeding. Coronavirus disease 2019 (COVID-19) is an illness caused by SARS-CoV-2. Though pneumonia and respiratory failure are major causes of morbidity and mortality, multisystemic complications were identified, including hematological ones. Several ITP relapse cases post-mRNA SARS-CoV-2 vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…70 The mRNA COVID-19 vaccines were also thought to trigger immune thrombocytopenia flares as a significant number of patients, known to have immune thrombocytopenia, had relapses within a year of receiving the second doses of either the BNT162b2 or the mRNA-1273 vaccines. 71 Furthermore, in a review of several studies, 66 patients were found to have immune thrombocytopenia after the administration of COVID-19 vaccination. 72 The mRNA vaccines were found to have triggered immune thrombocytopenia episodes more than other types of COVID-19 vaccines.…”
Section: Covid-19 Vaccines and Immune Thrombocytopeniamentioning
confidence: 99%
“…70 The mRNA COVID-19 vaccines were also thought to trigger immune thrombocytopenia flares as a significant number of patients, known to have immune thrombocytopenia, had relapses within a year of receiving the second doses of either the BNT162b2 or the mRNA-1273 vaccines. 71 Furthermore, in a review of several studies, 66 patients were found to have immune thrombocytopenia after the administration of COVID-19 vaccination. 72 The mRNA vaccines were found to have triggered immune thrombocytopenia episodes more than other types of COVID-19 vaccines.…”
Section: Covid-19 Vaccines and Immune Thrombocytopeniamentioning
confidence: 99%
“…We have read the research conducted by Hana Qasim et al 1 with great interest. We appreciate the author for sharing her experience and would like to share our outlook which has raised a few questions in our mind.…”
Section: Dear Editormentioning
confidence: 99%